A replaceable fuse steel-concrete composite connection: Force transfer mechanism and design considerations. (August 2021) - He, Xiuzhang; Ke, Ke; Guo, Lihua; Yam, Michael C.H.; Wang, Zhihui
Abstract: This study explored the load-carrying mechanisms of a seismic resistant steel-concrete composite connection with angle fuse elements at the bottom flange. The research was commenced by examining the test results of three full-scale test connections, in particular, the moment/force evolution responses of the connections were studied. Subsequently, detailed finite element (FE) models of the three full-scale test specimens were developed. The predictions by the FE analysis were in good agreement with the test results in terms of the hysteretic responses and the forces of the angles. Following the verification study, the results of the FE analysis were utilised to offer an in-depth insight into the behaviour of the connections, and the force transfer mechanism of the connection was examined. In particular, it was confirmed that the fuse angles could resist the applied moment via axial forces, and the shear resistance was mainly provided by the connection plates at the top flange in the inelastic stage. In addition, an analytical model for quantifying the connection resistance was developed. Design considerations were also proposed to offer design guides for practicing engineers Graphical abstract: Unlabelled Image Highlights: The stress distribution and force transfer mechanism of a novel connection was examined. The force evolution of the individual elements in the connection was clarified. A simplified beam model for quantifying the shear resistance of the connection plates was established. The design equations of the moment/shear resistance of the connection were proposed.